The Influence of Teacher’s Competence towards the Motivation of Students in Learning English - Bustami Usman; Tengku Maya Silviyanti; Marzatillah Marzatillah (Universitas Syiah Kuala, 2016)
This study is intended to find out the influence of the teacher’s competence towards the motivation of students in learning English. A questionnaire was given to 24 students at a sports school in Banda Aceh, Indonesia. The five (5) closed and open questions were adapted from Zhao (2012). The results from this study show that the competences of the teacher including cognitive, affective, and psychomotor competence (Syah, 2013) enhance the motivation of students to learn English. The teacher’s personality also has a strong influence on the students’ perceptions of their teacher. The teacher’s cognitive abilities which include the teacher’s competence at teaching English motivate the students to like English as a subject. Next, the teacher’s affection for the students also influences the students’ motivations who do not only like the subject but to like the teacher. Lastly, the teacher’s way of presenting lessons (psychomotor) affect the motivation of the students to learn English. Thus, it can be concluded that the teacher, as one of the external factors, should be able to maximize his/her competence in teaching to motivate the students more when learning English.